Glyphosate tolerant volunteer corn control at two development stages - Costa,N.V. (2014)
The loss of grains during the harvest of glyphosate tolerant corn may generate volunteer plants, which can interfere in the conventional or glyphosate crop in succession. The current work aim to evaluate the control of the volunteer corn glyphosate tolerant under two weed stages. Aimed to evaluate the control of volunteer glyphosate tolerant corn in two stages of development. There were conducted two experiments with hybrid 2B688 HR (lepidoptera and glyphosate tolerant), the application were at V5 and V8 stage. The experiment was randomized block design with four replicates, using the treatments: haloxyfop at 25, 50 and 62 g ha-1 alone and associated with 2,4-D at 670 g ha-1 or fluroxypyr at 200 g ha-1. The standard was clethodim at 84 g ha-1 with 2,4-D and fluroxypyr at same rates. The applications of haloxyfop and clethodim both isolated or in a mixture with 2,4-D and fluroxypyr at V5 stage showed total control (100%) at 32 and 39 days after the application, except for haloxyfop + 2,4-D (25 + 670 g ha-1) mixture, which did not provided adequate control. At V8 stage, haloxyfop + 2,4-D (50 + 670 g ha-1) and haloxyfop + 2,4-D (62 + 670 g ha-1) mixtures took up to 6 and 10 days or longer to reach adequate to excellent control, when compared to haloxyfop isolated applications in the same doses, respectively. Either isolated clethodim or mixed with 2, 4-D and fluroxypyr did not show adequate control. The treatments showed efficient control on volunteer corn plants at V5 stage, except for haloxyfop + 2, 4-D (25 + 670 g ha-1) mixture. At V8 stage applications, haloxyfop either isolated or mixture with fluroxypyr demonstrated excellent control on every evaluated dose. The mixture with 2, 4-D can reduce haloxyfop efficiency at low doses. Clethodim alone or mixed with 2,4-D or furoxypyr did not provide acceptable level of control.